PENGARUH PENGETAHUAN PERPAJAKAN, SANKSI PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KECAMATAN SONDER KABUPATEN MINAHASA - Mumu, Ablessy; Sondakh, Jullie J.; Suwetja, I Gede (Universitas Sam Ratulangi, 2020)
Tax has a very important role for development in Indonesia because tax is the biggest source of state revenue. Compliance with paying taxes is very important to increase the country's income and welfare. The purpose of this study was to determine the effect of tax knowledge, tax sanctions, and taxpayer awareness of tax compliance in paying land and building taxes. The research method is quantitative. The sample selection uses the accidental sampling method by distributing questionnaires to 100 land and building taxpayers in Sonder District, Minahasa Regency. The analytical method used is multiple linear regression analysis using the SPSS program. The results showed that tax knowledge, tax sanctions and awareness of taxpayers had a positive and significant effect on compliance with paying land and building taxes in Sonder District, Minahasa Regency.